Favorable Pulse Wave Augmentation Indices and Left Ventricular Diastolic Profile in β-Thalassemia Minor. (November 2017) - Chamaidi, Aikaterini; Karagiannis, Georgios; Christidi, Aikaterini; Parisis, Charalambos; Koutrakis, Konstantinos; Xanthopoulos, Andrew; Skoularigis, John; Giamouzis, Gregory; Triposkiadis, Filippos K.
Β-Thalassemia minor (β-Τm) is associated with rheological and biochemical alterations that can affect cardiovascular function. We aimed to evaluate the elastic arterial properties and the pulse wave augmentation indices in a population of patients with β-Τm. Seventy-five individuals with β-Τm (age 55.5 [42.75-65.25], women 48%) and 127 controls (age 57 years [48-63], women 55.1%) underwent comprehensive echocardiographic evaluation and applanation tonometry of the radial and femoral artery. Pulse wave analysis revealed that augmentation pressure, augmentation index (AIx), and heart rate–corrected AIx were significantly lower (median [interquartile range]: 8.75 [4.625-13] vs 11 [6.5-14.5], P = .017; 26.5 [17.5-33.375] vs 30.5 [20.75-37.5], P = .014; and 22.25 [15.125-29.5] vs 27 [20.5-33], P = .008, respectively) in the β-Τm group compared to controls. The left atrial active emptying volume was significantly lower and the isovolumic relaxation time was shorter in the β-Τm group compared to the control group (10.2 [7.4-14.4] vs 12.0 [8.6-15.8], P = .040 and 78 [70-90] vs 90 [70-104], P = .034, respectively). β-Thalassemia minor is associated with favorable pulse wave augmentation indices and left ventricular diastolic function profile in asymptomatic individuals with cardiovascular risk factors.